Створення ігрових додатків та віртуальна реальність - Задорожний, О. В. (ХНУРЕ, 2020)
A video game is an electronic game that involves interaction with a user interface to generate visual feedback on a two- or three-dimensional video display device such as a touchscreen, virtual reality headset or monitor set. For the last of more than 40 years, video games have become an increasingly important part of the entertainment industry. Games are produced through the software development process that starts from an idea or concept. Virtual reality is a simulated experience that can be similar to or completely different from the real world. Applications of virtual reality can include entertainment (i.e. video games) and educational purposes (i.e. medical or military training).